«It is art as well as a profession»: Conceptions of artistic work - the case of actors in Greece - Καρακιουλάφη, Χριστίνα (The Greek Review of Social Research, 2014)
Αrtistic work and the rules governing artistic labor markets are considered as a puzzle for those concerned with the sociology of professions or sociological approaches of salaried work. The major question is whether artistic work and artistic professions can be perceived with the common instruments and the frameworks of reference, analysis and interpretation which we use in the cases of other types of paid work. To examine this issue in this article we will focus on the actors' profession in Greece, giving emphasis on how the social subjects themselves conceive their work and profession.